2022
DOI: 10.2151/jmsj.2022-023
|View full text |Cite
|
Sign up to set email alerts
|

地上気温上昇に伴って観測された都市域極端降雨の増加:ジャカルタの事例

Abstract: Sub-daily extreme precipitation in Jakarta exhibits trends related to local temperature, seasonal tropical monsoon circulations, and other environmental drivers. Analysis of 81 years of hourly rainfall between 1900-2010 shows a significant increase of about doubling the number of short-duration rainfall events in the wet season. In recent decades, rainfall is found to be higher in intensity and shorter in duration relative to preceding decades. These short-duration rain showers develop typically between aftern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…An increase in urban temperature can affect rainfall intensity through the complex process of land-atmosphere interaction influenced by LULC change and urbanization. The results show consistency with previous research on the relationship between an increasing urban temperature and extreme rainfall intensity in Jakarta [57]. Siswanto et al (2022) [57] observed an increase in urban temperature with an increase in the atmospheric moisture content with an increase in extreme rainfall intensity in Jakarta between 1900 and 2010.…”
Section: Increasing Maximum Daily Temperature and Maximum Daily Rainfallsupporting
confidence: 91%
See 2 more Smart Citations
“…An increase in urban temperature can affect rainfall intensity through the complex process of land-atmosphere interaction influenced by LULC change and urbanization. The results show consistency with previous research on the relationship between an increasing urban temperature and extreme rainfall intensity in Jakarta [57]. Siswanto et al (2022) [57] observed an increase in urban temperature with an increase in the atmospheric moisture content with an increase in extreme rainfall intensity in Jakarta between 1900 and 2010.…”
Section: Increasing Maximum Daily Temperature and Maximum Daily Rainfallsupporting
confidence: 91%
“…The increasing urban temperature in Jakarta is associated with extreme rainfall [56][57][58]. Tsiringakis et al (2017) [56] studied urban flooding in Jakarta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the North Jakarta area is directly adjacent to Jakarta Bay so the water vapor availability is abundant. This causes the total water column to be high so that the frequency of rain also increases (Siswanto et al, 2022). Therefore, the North Jakarta and Central Jakarta areas have a high hazard class for experiencing flooding.…”
Section: Rainfall Intensitymentioning
confidence: 99%
“…Our findings will provide a foundation for future studies on interactions between the sea breeze and climate change and/or urbanization in Jakarta. Microclimate changes observed in Jakarta (Siswanto et al, 2022) may also influence the sea breeze (Darmanto et al, 2019); therefore, knowledge about seasonal sea breeze variation will be important for isolating the effects of climate change and urbanization, thus improving the accuracy of future analyses.…”
Section: Introductionmentioning
confidence: 99%